Mengungkap Aktivitas Antikanker Senyawa Dihidrokaempferida secara In Silico - Arif Fadlan; Tri Warsito; Sarmoko Sarmoko (Jambura Journal of Chemistry, 2022)
This study aims to perform molecular docking of dihydrokaempferide and to predict the ADMET profiles of dihydrokaempferide. The molecular docking was conducted on DAPK1 macromolecules (5AUX and 5AV3) by preparation of dihydrokaempferide, preparation of DAPK1, docking simulation of dihydrokaempferide, visualization of docking results, and ADMET analysis. The molecular docking of dihydrokaempferide produced a binding affinity value of -6.9 kcal/mol for 5AUX and of -5.7 kcal/mol for 5AV3. The ADMET prediction indicated dihydrokaempferide had good physicochemical properties according to the criteria of absorption, distribution, metabolism, excretion, and toxicity.